Emulsion Formation in Palm Oil Methyl Ester Sulfonate Surfactant to Light Crude Oil - Rini Setiati; Muhammad Taufiq Fathaddin; Berkah Hani (Journal of Earth Energy Science, Engineering, and Technology, 2023)
The Enhanced Oil Recovery method is a method that can be attempted to increase the recovery of petroleum. One of the materials that can be used is Methyl Ester Sulfonate surfactant from palm oil, as a vegetable surfactant whose raw materials are widely available in Indonesia. In this study, the compatibility test of Methyl Ester Sulfonate surfactant was carried out on light crude oil type T samples. The study was carried out with various surfactant concentrations, starting from 0.25%, 0.3%, 1%, 1.5%, and 2%. In the aqueous stability test, the results obtained for all clear conditions for the surfactant concentration were measured for 3 days in an oven with a temperature of 60oC. Whereas in the phase behavior test, good results of the upper phase emulsion were obtained at concentrations of 0.3%, 1%, 1.5%, and 2%. The volume of the top phase emulsion ranges from 25% to 37.5%. (Normal). From the results of this study, it can be concluded that for the crude oil sample T, palm oil MES surfactant is stable for use as a surfactant injection fluid, with a surfactant concentration composition that produces a fairly large upper phase emulsion of around 25% - 37.5% at a surfactant concentration of 0.5% - 2%.